Valores léxico- semánticos de figuras literarias en cantos tradicionales ecuatorianos. - Sarango Maza, Erika Nagely (2024)
The main objective of the research entitled: Lexical-semantic analysis of literary figures in traditional Ecuadorian songs was to analyze the lexical-semantic values found in the literary figures of the selected Ecuadorian songs. The research work was carried out using a qualitative approach and a non-experimental-descriptive design. In addition, a bibliographic and documentary search was carried out. For the collection of information, songs were compiled from Ecuadorian publications and records, specifically, songbooks of Ecuador. The lexical-semantic analysis provided interpretations related to the scarce information found at the beginning of the project; therefore, this version contributes to the proposed topic with several particularities, such as lexical analysis. The research shed light on the lexical-semantic richness of Ecuadorian traditional songs, provided new interpretations that linked culture with linguistic variety. The results obtained not only enriched the understanding of the literary figures present in these songs, but also highlighted the importance of preserving and studying the rich cultural heritage through its artistic expression. Furthermore, it broadened the academic knowledge in the field of linguistics and literature, therefore, it becomes a support for future studies and educational programs focused on the promotion and preservation of cultural identity; since the traditional Ecuadorian songs were assumed as artistic compositions and as linguistic archives that encapsulate the very essence of the cultural narrative of the people.